2022
DOI: 10.3390/photonics9070481
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response Effect of Photobiomodulation on Hemodynamic Responses and Glucose Levels in Men with Type 2 Diabetes: A Randomized, Crossover, Double-Blind, Sham-Controlled Trial

Abstract: This study verifies the acute dose response effect of photobiomodulation (PBM) by light emitting diodes (LEDs) on hemodynamic and metabolic responses in individuals with type 2 diabetes mellitus (T2DM). Thirteen participants with T2DM (age 52 ± 7 years) received PBM by a light-emitting diode array (50 GaAIAs LEDs, 850 ± 20 nm, 75 mW per diode) on the rectus and oblique abdomen, quadriceps femoris, triceps surae, and hamstring muscle areas, bilaterally, using different energy treatments (sham, 75, 150, 300, 450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The findings of the current study showed an improvement in LV function after LLLT, which may be explained by the release of nitric oxide, which causes peripheral vasodilatation, reduces peripheral resistance, and then improves cardiac output [22]. Also, may be explained by an improvement in cardiac muscle performance due to the increased intake of energy provided by the increased aerobic metabolism stimulated by LLLT [9,23].…”
Section: Discussionmentioning
confidence: 83%
“…The findings of the current study showed an improvement in LV function after LLLT, which may be explained by the release of nitric oxide, which causes peripheral vasodilatation, reduces peripheral resistance, and then improves cardiac output [22]. Also, may be explained by an improvement in cardiac muscle performance due to the increased intake of energy provided by the increased aerobic metabolism stimulated by LLLT [9,23].…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, to ensure the high quality of this trial, we will employ principles of intention-to-treat analysis [ 111 ]. Also, the PBMt parameters that will be used have been repeatedly reported to potentiate the positive effects of strength training in humans [ [51] , [52] , [53] , [54] ], and were recently reported to exert positive effects on glucose metabolism in T2DM patients [ 46 ]. Finally, the strength training protocol that will be prescribed is based on international guidelines [ 21 , 32 , 34 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, improvements in inflammatory parameters are also reported with PBMt [ 40 ]. Recently, different research groups have demonstrated that treatment with PBMt reduced IR and improved glucose metabolism in mice fed a high-fat diet [ [41] , [42] , [43] , [44] , [45] ] and in T2DM patients [ 46 ]. Furthermore, results showed there was an improvement in mitochondrial function in skeletal muscle, greater activation of the insulin pathway in adipose tissue and skeletal muscle, less inflammation in adipose tissue, and less visceral adiposity [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…PBMt is known to have a biphasic doseresponse [37,38] which is responsible for stimulatory, inhibitory, or even null biological effects. Recently, using a randomized, crossover, double-blind, sham-controlled trial our group [36] reported a dose-response effect of PBMt on glycemia in T2DM patients, where we showed that low and moderate-to-high, but not moderate or high, doses of PBMt reduced glycemia. Furthermore, there is evidence that PBMt effects are also time-dependent [39,40].…”
Section: Introductionmentioning
confidence: 85%
“…Many studies using animal models have shown improved glucose metabolism in response to PBMt [27][28][29][30][31][32][33][34][35], and one clinical trial [36] has supported the potential clinical use of PBMt for improving glucose metabolism. PBMt is known to have a biphasic doseresponse [37,38] which is responsible for stimulatory, inhibitory, or even null biological effects.…”
Section: Introductionmentioning
confidence: 99%